Condition, not eyespan, predicts contest outcome in female stalk‐eyed flies, Teleopsis dalmanni. Issue 9 (8th April 2015) - Bath, Eleanor; Wigby, Stuart; Vincent, Claire; Tobias, Joseph A.; Seddon, Nathalie
Abstract In contests among males, body condition is often the key determinant of a successful outcome, with fighting ability signaled by so‐called armaments, that is, exaggerated, condition‐dependent traits. However, it is not known whether condition and exaggerated traits function in the same way in females. Here, we manipulated adult condition by varying larval nutrition in the stalk‐eyed fly, Teleopsis dalmanni, a species in which eyespan is exaggerated in both sexes, and we measured the outcome of contests between females of similar or different body condition and relative eyespan. We found that females in higher condition, with both larger bodies and eyespan, won a higher proportion of encounters when competing against rivals of lower condition. However, when females were of equal condition, neither eyespan nor body length had an effect on the outcome of a contest. An analysis of previously published data revealed a similar pattern in males: individuals with large relative eyespan did not win significantly more encounters when competing with individuals of a similar body size. Contrary to expectations, and to previous findings in males, there was no clear effect of differences in body size or eyespan affecting contest duration in females. Taken together, our findings suggest that although eyespan can provide an honest indicator of condition, large eyespans provide no additional benefit to either sex in intrasexual aggressive encounters; body size is instead the most important factor.